Telemedicine in pediatric cardiology - Maniar Urvi Dilip. (2008)
In this project, the symptoms, diagnosis and monitoring method used for eight common lesions, which account for 85 percent of congenital heart disease are discussed. These include Atrial Septal Defect (ASD), Ventricular Septal Defect (VSD), Patent Ductus Arteriosus (PDA), pulmonary valve stenosis, and Aortic valve stenosis, Coarctation of aorta, Tetralogy of Fallot and Transposition of great arteries. Cardiac monitoring and treatment methods along with symptoms and diagnostic tools for acquired heart diseases like Kawasaki Syndrome, Myocarditis and Fast Arrhythmias are also discussed.